2019
DOI: 10.1177/1362361319833929
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perceptions of raising children with autism spectrum disorders in the United States and Arab countries: A comparative review

Abstract: Four databases were searched to identify studies published by Arab researchers on parents’ perceptions of autism spectrum disorder and studies conducted by US researchers and published in systematic reviews of this topic. The electronic search resulted in 14 studies published by Arab researchers and 55 studies published by US researchers. The results showed that autism spectrum disorder has many of the same effects on Arab and American families. Six major areas were identified in the results. Financial difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 98 publications
(226 reference statements)
2
22
0
1
Order By: Relevance
“…Our findings are consonant with research evidence that access to educational activities for children with ASD and their consistency depends on socio-cultural, economic, and individual factors (Barry et al, 2020;Dawson et al, 2010;Khateeb et al, 2019), and that parental beliefs and attitudes are likely to affect their education. This study also provides evidence of such an effect in extraordinary circumstances, such as a pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings are consonant with research evidence that access to educational activities for children with ASD and their consistency depends on socio-cultural, economic, and individual factors (Barry et al, 2020;Dawson et al, 2010;Khateeb et al, 2019), and that parental beliefs and attitudes are likely to affect their education. This study also provides evidence of such an effect in extraordinary circumstances, such as a pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…Many studies contained reports from parents (predominantly mothers) of feelings of self‐blame, depression, and an adverse impact on life satisfaction (Ilias et al, 2018; Liao, Lei, & Li, 2019; Nuri, Batorowicz, & Aldersey, 2019; Scherer, Verhey, & Kuper, 2019). A review of studies from the Middle East comprise, by contrast, a majority of fathers as respondents, and reflected more stress related to financial pressures (Al Khateeb, Kaczmarek, & Al Hadidi, 2019). The large impact of economic factors on family quality of life also emerged as a finding from a review on families with a child living with a disability in the Global South (Hunt & Watermeyer, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Another key roadblock is the lack of autism or disability‐specific rights legislation or, in countries where disability‐specific laws were in place, an absence of support for the implementation of these policies (Bakare et al, 2019). This is compounded by low levels of awareness of autism even within the health system, in both frontline healthcare workers and professionals, with very limited opportunities for training (Al Khateeb et al, 2019; de Leeuw et al, 2020; Shorey et al, 2020; Wang, Hedley, Bury, & Barbaro, 2020), resulting in a lack of any established models of developmental surveillance. In LAMIC, the lack of a right to UHC leads to financial burden on families, since most autism services are privately accessed and result in prohibitive out of pocket expenses (Bakare et al, 2019; Hunt & Watermeyer, 2017; de Leeuw et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been observed that primary caregivers, especially the mothers, get frustrated due to unawareness of behavioral issues appearing in child with ASD at the age of 2 years than a healthy child. 12 After careful review of the literature regarding the impacts of ASD on primary caregivers, it has been found that no such correlational study has been conducted in Pakistan. Currently, primary caregivers are facing stressful psychological issues, such as stress due to maladaptive behaviors of their autistic child, misdiagnosis, and improper access to healthcare facilities.…”
Section: Introductionmentioning
confidence: 99%